Pope Hadrian from the church of St. Archangel Michael in the monastery of Dolna Beshovitsa (Research Announcements "Heritage BG", 2025)
Amongst the surviving murals in the Church of Archangel Michael in the Monastery near the village of Dolna Beshovitsa is a preserved frieze with medallions of hierarchs. According to the inscriptions on part of them, they depict bishops of the Roman church. These are Pope Sylvester, Pope Hadrian as well as one more hierarch, whose inscription is only partly preserved (here the name is read as Pope Agatho). The main hypothesis the paper discusses is related to the depiction of Pope Hadrian – his presence in the altar space of the church, the possible answers to the questions: why exactly Pope Hadrian and his links to two of the images of hierarchs in the southern procession of Melismos, which are supposed to present St. Constantine-Cyril the Philosopher and St. Methodius. Furthermore, particular textual sources for the depiction of the Roman bishop are commented on, which expectedly are limited to the hagiographical texts of both brothers, because Pope Hadrian II is not part of the hierarchs listed in the Synaxaria. An assumption has been made about the existence of a common hagiographic source according to the hypothetical depiction of Pope Agatho. The depictions of Roman bishops in the Church of Dolna Beshovitsa, atypical forthe post-Byzantine churches, apartfrom that of St. Sylvester, raises the question about the mechanisms of inclusion of bishops in the altar programmes and the integration of images in the general scheme of connotations, established through the choice of certainhierarchs, and the possibilities this particular systemnot just to reconstruct, but also to generate novel ones in a new context. References:Primary sources:Kliment Ohridski (1973). Sabrani sachinenia. Sast. B.S. Angelov, K.M. Kuev, H. Kodov. Sofia.Stara Balgarska literatura (1986). Stara Balgarska literatura. T. 4. Sofia.Delehaye, H. (1902). Synaxarium ecclesiae Constantinopolitanae. In: Propylaeum ad Acta Sanctorum. Novembris. Bruxelles.Dionysiou tou ek Fourna (1909). Ermeneia tes zografikes tehnēs. Ekd. ypo A. Papadopoulou-Kerameōs. Petroupolei.Secondary sources:Angelov, Bonyu St. Slavyanski izvori za Kiril Metodiy. – Izvestia na Darzhavna biblioteka „Vasil Kolarov“ (1956). Sofia, 179-215.Angelov, Bonyu St., Hristo Kodov (red.) Kliment Ohridski. Sabrani sachinenia. T. 3. Prevod, obrabotka komentari varhu Prostrannoto zhitie na Konstantin-Kiril Filosof Prostrannoto zhitie na Metodiy. Sofia, 160-168, 203-212.Bakalova, Elka. Stenopisite na tsarkvata pri selo Berende. Sofia.Vasiliev, Asen. Tsarkvi manastiri iz Zapadna Bulgaria. In: Razkopki prouchvania. T. 4. Sofia, 4-114.Vasiliev, Asen. Obrazi na Kiril Metodiy chuzhdoto nasheto izobrazitelno izkustvo. In: Hilyada sto godini slavyanska pismenost 863–1963. Sbornik chest na Kiril Metodiy. Sofia, 393-488.Voyvodich, Dragan. Zidno slikarstvo tsrkve Svetog Ahilija Airљu. Belgrade.Grozdanov, Tsvetan. Kurbinovo drugi studii za freskozhipovisot vo Prespa. Skopje.Gyuzelev, Vasil. Papstvoto balgarite prez Srednovekovieto. Plovdiv.Duychev, Ivan. Kam talkuvaneto na prostrannite zhitia na Kirila Metodia. In: Hilyada sto godini slavyanska pismenost 863–1963. Sbornik chest na Kiril Metodiy. Sofia, 295-304.Zlatarski, Vasil N. Slovenskoto zhitie na sv. Nauma ot XVI vek. – Spisanie na Balgarskata akademia na naukite, No. 30/17, 1-28.Ivanova, Klimentina, Svetlina Nikolova (red.) Tarzhestvo na Slovoto. Zlatniyat vek na balgarskata knizhnina. Sofia.Ivanova, Maya. Kirilskite fragmenti ot Prostrannoto zhitie na Konstantin-Kiril – nauchna problematika. – Kirilo-Metodievski studii, No. 20, 88-115.Ivanova, Maya. Tekstologicheski problemi Prostrannoto zhitie na Konstantin-Kiril Filosof. – Kirilo-Metodievski studii, No. 22 (Kirilo-Metodievski izvori, t. 1).Kosova, Alda Dzhambelika. Edin izryaden starobalgarski katehizis: Prologat na MATY I ZhITI~ BLAZhENAGO OTATsA NAShEGO I OUChITELA ME0ODIІA, ARHIEPISKOPA MORAVYSKA. In: Cyrillo-Methodian Studies. T. 17, Sofia, 408-424.Kuneva, Tsveta. Stenopisite Dolnobeshovishkia manastir „Sv. Arhangel Mihail“. – Problemi na izkustvoto, No. 2, 26-30.Lavrov, Petro. Kirilo ta Metodiy davnyo-slavyansykomu pisymenstvi. Kyiw.Loseva, Olga.V. Russkie Mesyatseslovy XI–XIV vekov. Moskva.Luhovitski, Lev V. Grecheskiy original „Napisanie pravoy vere“ Konstantina Filosofa: strukturnaya organizatsia polemicheskie zadachi. – Slavyanovedenie, N 5, 65-73.Mardi-Babikova, Velda. Kam vaprosa za obraza na Konstantin Kiril Filosof. – Problemi na izkustvoto, No. 1, 32-37.Penkova, Biserka. Stenopisite bachkovskata trapezaria atonskata traditsia. – Problemi na izkustvoto, No. 1, 46-53.Penkova, Biserka. Bachkovski manastir, trapezaria. In: Korpus na stenopisite ot XVII v. Bulgaria (red. B. Penkova, Ts. Kuneva). Sofia, 131-137.Smyadovski, Stefan. Nadpisite kam izobrazheniyata na vselenskite sabori v Eleshnishkia manastir (XVI v.) – izvori problemi. Starobalgaristika, No. 17, 77-83.Smyadovski, Stefan. Izobrazhenie – nadpis – yerarhia (epigrafsko-agiolozhki belezhki). – Starobalgarska literatura, No. 28/29, 137-142.Cheshmedzhiev, Dimo. Kiril Metodiy balgarskata istoricheska pamet prez srednite vekove. Sofia.Hristova-Shomova, Iskra. Sluzhebniyat Apostol slavyanskata rakopisna traditsia. T. II. Izsledvane na sinaksarite (hristiyanskite praznitsi slavyanskite apostoli). Sofia.Češmedžiev, Dimo. La contamination entre Constantin-Cyrille le Philosophe et Cyrille d’Alexandrie et sa répercussion dans l’art balkanique médiéval. – Etudes balkaniques, No. 1, 45-59.Dvornik, Francis. Les légends de Constantin et de Méthode vues de Byzance. Prague.Dvornik, Francis. The Ecumenical Councils. New York.Hefele, Charles Joseph. A History of the Christian Councils, from the Original Documents, to the Close of the Council of Nicea, A.D. 325 (transl. from German by William R. Clark). Second ed., revised. Edinburg.Mylona, Zoe A. The Zakynthos Museum. Athens.Rousseva, Ralitsa. Cyril and Methodius in Historical Iconography. In: Celebrating the Legacy of Cyril and Methodius with Special Reference to Historical Iconography. San Antonio Palace, Attard, 12 – 13 May 2017 (ed. by L. Bianco). Valetta.Todić, Branislav. Représentations de Papes Romains dans l’église Sainte-Sophie d’Ohrid. Contribution à l’idéologie de l’archevêchê d’Ohrid. – Δελτίον της Χριστιανικής Αρχαιολογικής Εταιρίας, No. 29, 105-118.Walter, Christopher. L’iconographie des conciles dans la tradition byzantine. Paris.Walter, Christopher. A Portraits of Local Bishops: A Note on Their Significance. – Зборник радова Византолошког института [Zbornik radova Vizantoloshkog instituta], No. 21, 7-17.
Keywords: St. Archangel Michael church; Dolna Beshovitsa; pope Adrian; pope Agathon; pope Silvester; Sts Cyril and Methodius; Ecumenical councils; textual sources